The electrical resistance of spatially varied magnetic interface. The role of normal scattering - Gurzhi, R.N.; Kalinenko, A.N.; Kopeliovich, A.I.; Pyshkin, P.V.; Yanovsky, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We investigate the diffusive electron transport in conductors with spatially inhomogeneous magnetic properties taking into account both impurity and normal scattering. It is found that the additional interface resistance that arises due to the magnetic inhomogeneity depends essentially on their spatial characteristics. The resistance is proportional to the spin flip time in the case when the magnetic properties of the conducting system vary smoothly enough along the sample. It can be used to direct experimental investigation of spin flip processes. In the opposite case, when magnetic characteristics are varied sharply, the additional resistance depends essentially on the difference of magnetic properties of the sides far from the interface region. The resistance increases as the frequency of the electron-electron scattering increases. We consider also two types of smooth interfaces: (i) between fully spin-polarized magnetics and usual magnetic (or non-magnetic) conductors, and (ii) between two fully oppositely polarized magnetic conductors. It is shown that the interface resistance is very sensitive to appearing of the fully spin-polarized state under the applied external field.